Histological Structure of Gills of Giant Mudskipper (Periophthalmodon schlosseri) - Danang Bagus Yudistira; Anni Nurliani; Heri Budi Santoso (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Giant mudskipper (Periophthalmodon schlosseri) is one of gobiidae members that does air-breathing and lives on intertidal zone with mangrove habitat. The ability of giant mudskipper to adapt with water to land environment is due to its gill histological structure. The objective of the present study was to observe the structure of giant mudskipper’s gill and to identify sort of cells and its distributions descriptively. The gills of three adult giant mudskippers were taken and processed to histological slides with 4 µm thickness each. Samples were stained with hematoxyline-eosin (HE) method. The results indicated that Mudskipper gills consist of epithelial cells, such as squamous and cuboid on the lamellae surfaces contiguous with mucous and chloride cells that are spread at interlamellae zone and peripheral surfaces of fused secondary lamellae of mudskipper gills. Pillar cells sre found inside of secondary lamellae and form lacunae that split secondary lamellae with block to block spaces that fill with erythrocytes. Hyaline cartilages are found to form canals for transport veins inside primary lamellae and soft muscle connecting hyaline to basal membrane of primary lamellae surfaces. The difference of histological structures between giant mudskipper gills to other aquatic osteichthyes is that the secondary lamellae is fused in normal (non-pathological) condition. The fusion makes epithelial cells of the econdary lamellae are thicker. The fusion also makes oxygen diffusion path from water to capilary vein is a bit longer about 10µm. The thickness of epithelial cells of secondary lamellae makes the mudskippers gills not an efficient organ for gas exchanges in water, but it is important in osmoregulation. Keywords: Periophthalmodon schlosseri, air-breathing, histological structure, lamellae fusion, osmoregulation.